Volume Estimation Using Resistivity Tomography Method In Bakauheni, South Lampung - Ependy, Julpan; Rustadi, Rustadi; Wibowo, Rahmat Catur (Journal of Engineering and Scientific Research, 2025)
Lampung is an area that has various natural resources, one of which is andesite rock. National economic growth and incessant infrastructure development have resulted in an increased need for building materials, including Andesite. Andesite rocks are widely used for the formation of building foundations, making bridges, and paving roads. In this study, the volume of andesite rocks was calculated using the resistivity tomography method in the Bakauheni area of South Lampung in Pegantungan, Bakauheni District, South Lampung Regency, Lampung Province. which consists of 5 lines with a spacing between electrodes of 5 meters, with a span length of about 315 meters. The apparent resistivity data obtained are processed into a two-dimensional model through linear inversion using RES2DINV software. The two-dimensional model was then interpolated using the Rockworks 15 tool to become a three-dimensional model. Based on the 2D cross-section model, the high resistivity values varied. identified as andesite rock, which is imaged in red to purple colour, and volumetric andesite rock based on 3D interpolation for an area of ± 15.20 Ha is 3,411,066.876 m3.